Immediate effects of 850 nm Diode Laser on patients with Cervical Myofascial Pain Syndrome: a Randomized-controlled trial (Bangladesh Journal of Medical Science, 2024)
Objectives  Myofascial pain syndrome (MPS) is one of the most common causes of chronic neck pain. Low level laser therapy (LLLT) is a physical therapy modality that can be used to reduce pain and improve function of patients with MPS. The aim of this study was to assess and evaluate the effects of LLLT added to the conventional physical therapy in comparison with the conventional physical therapy alone on pain intensity, pressure pain threshold (PPT) and cervical range of motion (ROM) in cervical MPS patients.Methods and Materials  Twenty-four adults diagnosed with cervical MPS according to Travell and Simons’ criteria were randomized into 2 equal groups; Group A: receive LLLT on upper trapezius trigger points with conventional physical therapy, while Group B: receive conventional physical therapy alone. Measured outcomes were pain, PPT and cervical flexion and extension ROM, using Numerical Rating Scale (NRS), Algometer and Goniometer, respectively. Outcomes were measured pre-treatment and immediately post-treatment.Results and Discussion  A significant improvement in the pain, PPT and cervical flexion and extension were observed in all groups after treatment, compared to the pre-treatment values (P < .05). However, there was no significant difference between the study groups post treatment for all measured outcomes.Conclusion  Low-level laser therapy is not considered a beneficial extension to the standard conventional therapy on active MPS as it didn’t add to the immediate effect of conventional physical therapy on pain, PPT and ROM in patients with cervical MPS.Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 337-344